In Silico Designing of CRISPR Grna And Vector to Knockout Tetracycline Resistant Gene (Teta Gene) Of Escherichia Coli - Choushette, Bhaurao B.; Solunke, Sarita L.; P. Bhagat, Rahul; Satpute, Rajendra A. (Journal of Neonatal Surgery, 2025)
The rise in antibiotic resistance is major issue, primarily driven by the horizontal gene transfer. Antibiotic resistance can’t be eliminated as long as antibiotics continue to be used for treating infectious diseases. TetA gene, encoding the efflux carrier in plasma membrane of bacteria, is major contributor of resistance against the tetracycline. E. coli, one of the opportunistic pathogens, presents serious threat to healthcare due to resistance against various antibiotics including tetracycline. CRISPR cas system, a form of bacterial acquired immunity, has gained much attention recently for its potential use in overcoming the spread of antibiotic resistance genes. In the present study, we performed in-silico gRNA and vector designing specific to TetA gene of E. coli to determine the effect of CRISPR cas system on spread of antibiotic resistance. Three computational tools, ChopChop Crispor and Benchling, were used to design the gRNAs. These in-silico tools were employed to predict a relevant list of gRNAs targeting the TetA gene. Furthermore, the RNA fold web service was used to analyse the secondary structures of the lead single guide RNAs (sgRNAs) and gRNA1 was identified as the best candidate. The selection of the lead guide RNA involved designing target-specific oligonucleotides and sgRNAs using the NEBioCalculator tool. Subsequently, an in-silico construction of the guide RNA expression vector was carried out using SnapGene software. However, in vitro studies are required to determine whether the computationally predicted guide RNAs can effectively inhibit the TetA gene.